ASSOCIATION OF UREMIC PRURITIS IN HEMODIALYSIS PATIENTS WITH HEPATITIS C VIREMIA: ONE EGYPTIAN CENTRE EXPERIENCE - NAHALA ANBER; MOSTAFA ABDELSALAM; AHMED ABD EL-WAHAB; MAYSAA EL SAYED ZAKI (International Journal of Pharma and Bio Sciences, 2016)
Pruritis is a common complaint in uremic patients. Various pathogenic factors are claimed to be associated with complaint. Hepatitis C virus infection may be a predisposing factor for such complaint. The aim of the present study was to investigate the prevalence of pruritis in ESRD patients under hemodialysis in one Egyptian center and to correlate its association with the presence of hepatitis C viremia. This cross sectional study was conducted on ninety three patients attending Mansoura University hospital, Mansoura Nephrology and Dialysis Unit, Egypt from January 2015 till August 2015. The patients were subjected to full clinical examination and virological studies for hepatitis C virus (HCV) IgG and detection of HCV viremia by nested reverse transcriptase polymerase chain reaction (nested RT-PCR). Prutitis complaint was present among the majority of patients 86 (92.5%). HCV IgG was positive in more than half of the patients 51 (54.8%) with positive HCV viremia in 28 (30.1%). In comparison between patients with pruritis and patients without, HCV IgG , HCV RNA and duration of dialysis had high significant association with pruritis (P=0.0001 for each). The present study highlights the high prevalence of prutitis in patients under hemodialysis. The distinguished finding of the present study is the high significant association of hepatitis C viremia with pruritis in patients under hemodialysis. Future multicenters studies are recommended to elucidate the significance of this finding.